Private equity challenge: leveraging the highly integrated value chain of the Navigator company - exit options - Góis, Leonor Maria dos Santos (2023)
This paper consists of a proposed Investment Committee Paper, for academic purposes only, studying a private equity deal, analyzing a Leveraged Buyout of The Navigator Company, a leading pulp and paper Portuguese manufacturer with a highly integrated value chain. By creating value with a strategic buy-and-build plan, operational enhancement initiatives and leveraging organic growth opportunities an IRR of 23.1% and a MM of 2.8x can be achieved over a five-year investment period. Moreover, an individual in-depth analysis on Exit Options is included.